Healthy Vaginal Microbiota and Influence of Probiotics Across the Female Life Span - Lehtoranta, Liisa; Ala-Jaakkola, Reeta; Laitila, Arja; Maukonen, Johanna (Frontiers in Microbiology, 2022)
Vaginal microbiota plays a central role in women’s health and reproduction. Vaginal microbiota is dynamic and shaped by hormonal shifts in each stage of woman’s life from prepuberty to postmenopause. The current research has mainly focused on vaginal bacterial and fungal members of the community and emphasized their role in disease. However, the impact of balanced vaginal microbiota on health and its interaction with the host is yet poorly understood. High abundance of vaginal lactobacilli is most strongly associated with health, but the concept of health may vary as vaginal dysbiosis may be asymptomatic. Furthermore, there are a lot of variation between ethnic groups in terms of dominating vaginal bacteria. Probiotic lactobacilli could be safe and natural means to balance and maintain healthy vaginal microbiota. Research evidence is accumulating on their role in supporting women’s health throughout life. This review describes the current literature on the vaginal microbiota, the major factors affecting the composition, and how the communities change in different life stages. Furthermore, we focused on reviewing available literature on probiotics and their impact on vaginal microbiota and health.